Accurate Measurement of Cell Number–Normalized Differential Gene Expression in Cells Treated With Retinoic Acid - Nina Weichert-Leahey; Mark Zimmerman; Alla Berezovskaya; A. Look; Brian Abraham (Bio-Protocol)
Genome-wide gene expression analysis is a commonly used method to quantitatively examine the transcriptional signature of any tissue or cell state. Standard bulk cell RNA sequencing (RNA-seq) quantifies RNAs in the cells of the tissue type of interest through massive parallel sequencing of cDNA synthesized from the cellular RNA. The subsequent analysis of global RNA expression and normalization of RNA expression levels between two or more samples generally assumes that cells from all samples produce equivalent amounts of RNA per cell. This assumption may be invalid in cells where MYC or MYCN expression levels are markedly different and thus, overall mRNA expression per cell is altered. Here, we describe an approach for RNA-seq analysis of MYCN-amplified neuroblastoma cells during treatment with retinoic acid, which causes dramatic downregulation of MYCN expression and induces growth arrest and differentiation of the cells. Our procedure employs spiked-in RNA standards added in ratio to the number of cells in each sample prior to RNA extraction. In the analysis of differential gene expression, the expression level of each gene is standardized to the spiked-in RNA standard to accurately assess gene expression levels per cell in conditions of high and low MYCN expression. Our protocol thus provides a step-by-step experimental approach for normalizing RNA-seq expression data on a per-cell-number basis, allowing accurate assessment of differential gene expression in cells expressing markedly different levels of MYC or MYCN.